Surface Microstructure Study of Polyethylene Blends for Developing Environmental Degradable Plastic Bags (Journal of Chemical Engineering, 2013)
The morphology of the polymer blends retrieved from degradation experiments was investigated by studying the fractured surfaces using Scanning Electron Microscope for investigating the degradability of environmentally degradable plastic bags. We study the influence of adding photodegradable additives to film grade polyethylene under natural weathering conditions in Saudi Arabia. The films were exposed in outdoor environments located in Dhahran, Saudi Arabia. Comparison of different additives was determined and the additive PDQ-H shows the highest performance on the basis of degradation rate in the harsh environment of Saudi Arabian desert. DOI: http://dx.doi.org/10.3329/jce.v27i1.15847 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 8-11